A Simplified Model for Investigating the Magnetic Field Morphology of a Massive Clump in an Infrared Dark Cloud - Abdolreza Sharifi; Mohsen Nejad-Asghar (Iranian Journal of Astronomy and Astrophysics)
Observational results of the infrared dark clouds (IRDCs) reveal that these clouds exhibit a clumpy structure with directional line-of-sight velocity gradients. Recent research by Vahadanian & Nejad-Asghar~(2022, hereafter VN22) focused on the observational results of IRDC G34.43+00.24 (G34). The study concluded that G34 behaves like a rolling cylinder within the plane of the Galaxy,exhibiting a slow angular velocity of approximately $Ω\sim 5.7× 10^{-14}\, s^{-1}$. Using a simplified approximation for the mismatch of opposite charges, denoted by the parameter $ζ$, researchers demonstrated that the rotation-induced electric current can generate magnetic fields with strengths on the order of thousands of micro-Gauss in certain regions of G34. This study specifically examines the clumps within the IRDCs and employs a simplified model that incorporates a density-dependent function for the parameter $ζ$. Our research focuses on analyzing the magnetic field morphology within a clump. To address this investigation, we examine three specific clumps - MM1, MM2, and MM3 - within G34. The findings reveal that the magnetic field strength is higher near the axis of rotation compared to distant regions from the axis. Additionally, increasing values of the angular velocity $Ω$ and the mismatch of opposite charges $ζ$ lead to stronger magnetic field strengths. On the other hand, the results indicate that the strength of the magnetic field is not significantly influenced by the angle between the rotational axis of the IRDC and the boundary magnetic field. These findings offer valuable insights for researchers studying the distribution of star-forming cores within clumps.